2001
DOI: 10.1128/jcm.39.12.4500-4505.2001
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Serotypes and Virulence-Associated Factors: Detection of Genetic Diversity among O153:H45 CFA/I Heat-Stable Enterotoxigenic Escherichia coli Strains

Abstract: Characterization of enterotoxigenic Escherichia coli (ETEC) has been based almost exclusively on the detection of phenotypic traits such as serotypes and virulence-associated factors: heat-labile (LT) and heatstable (ST) toxins and colonization factors (CFs).In the present work we show that the analysis of band patterns generated by randomly amplified polymorphic DNA (RAPD) analysis and pulsed-field gel electrophoresis (PFGE) of digested chromosomal DNA can be used to detect genetic diversity among ETEC strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 30 publications
3
20
0
1
Order By: Relevance
“…Even if they did not belong to the same cluster, it seems likely that they were clonally closely related and probably belonged to the same clonal group. CFA/I-positive strains isolated in different geographical areas also are often closely related (14,16,21). In this study, we found that CFA/I-positive strains isolated from children in India (21) clustered together with our West African CFA/I-positive strains.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Even if they did not belong to the same cluster, it seems likely that they were clonally closely related and probably belonged to the same clonal group. CFA/I-positive strains isolated in different geographical areas also are often closely related (14,16,21). In this study, we found that CFA/I-positive strains isolated from children in India (21) clustered together with our West African CFA/I-positive strains.…”
Section: Discussionsupporting
confidence: 48%
“…Serotyping is a commonly used method for indicating clonal relatedness between bacteria, including ETEC. Although there are indications that ETEC strains that share the same serotype often are clonally closely related (14,15,16,21), it seems likely that clonally related strains may also have different serotypes, similar to what has been found for Shigella strains (19).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Macrorestriction profiling of genomic DNA was performed with the restriction endonuclease XbaI, as described previously (24). DNA was resolved by PFGE with a CHEF-DRII apparatus (Bio-Rad Laboratories, Richmond, CA).…”
Section: Methodsmentioning
confidence: 99%